A SURVEY ON FINGERPRINT PATTERN RECOGNITION - Dey, Swarnadip; Karmakar, Sajal Kumar; Goon, Surajit; Kundu, Prianka (International Journal of Research -GRANTHAALAYAH, 2019)
In this advance technical time, we all need accuracy to any security system. Among all security system, biometric recognition process is very popular in that time. Not only security purpose, identification is the main cause of using biometric characteristic. A pin, password combination is not enough to secure all things because that’s tracking is possible, but a person biometric characteristic is unique, so it is near to impossible to by-pass. In this paper, we discuss about the fingerprint types such as arch, loop, and whorl. We also discuss how the fingerprint will be recognized; however, where this technique is used in very large scale and what is the future scope of this technique, we discuss what improvement is needed in future.